Critically ill patients with COVID-19 with ECMO and artificial liver plasma exchange: A retrospective study. Issue 26 (26th June 2020) - Liu, Jian; Dong, Yong-Quan; Yin, Jie; He, Guojun; Wu, Xiaoxin; Li, Jianping; Qiu, Yunqing; He, Xuelin
Abstract : Abstract: COVID-19 is an emerging infectious disease capable of causing severe pneumonia. We aimed to characterize a group of critically ill patients in a single-center study. This was a retrospective case series of 23 patients with confirmed COVID-19-related critical illness in the intensive care unit (ICU) of a hospital in Hangzhou Zhejiang Province between January 22 and March 20, 2020. Of the 23 critically ill patients, the median age was 66 years (interquartile range [IQR] 59–80 years). The median time from disease onset to ICU admission was 10 days (IQR 6–11 days), to mechanical ventilation (MV) was 11 days (IQR 7.75–13 days), to artificial liver plasma exchange was 12 days (IQR 9.75–14.75 days), and to extracorporeal membrane oxygenation (ECMO) was 22 days (IQR 17.5–30 days). Nine patients required high flow oxygen. Fourteen patients received MV. Six required ECMO. Nine received artificial liver plasma exchange. Mortality was 0 at day 28. Mortality was 0 at day 28 in our single-center study. Extracorporeal membrane oxygenation reduced the requirements for ventilator support. Artificial liver plasma exchange significantly reduced inflammatory cytokine levels. These supportive therapies helped to extend the patients' survival times and increase the chance of follow-up treatments. Abstract : Supplemental Digital Content is available in the text